The changes in psychological symptoms of COVID-19 patients after “re-positive” - Wang, Xing; Fan, Qinyi; Li, Yunyue; Xiao, Junjian; Huang, Yanyan; Guo, Tiantian; Chen, Hongguang; Li, Mengqian (Frontiers in Psychiatry, 2022)
Background: Previous studies have showed that individuals infected with COVID-19 were more likely to report psychological symptoms. However, little is known about the changes from testing positive to negative to positive again. Methods: This survey was conducted through the questionnaires including the 7-item Generalized Anxiety Disorder (GAD-7), the 9-item Patient Health Questionnaire (PHQ-9), as well as the Self-Rating Scale of Sleep (SRSS) to explore the psychological status of COVID-19 and re-positive cases. ″re-positive″is defined as a positive RT-PCR test at any time during the recovery period after testing negative. Results: A total of 94 COVID-19 patients presented the prevalence rates of anxiety, depression, insomnia, and any of the three psychological symptoms being 26.6%, 8.6%, 12.8%, and 31.9%, respectively. Among these, 32 cases were re-tested positive during the recovery period, with the prevalence rates of anxiety, depression, insomnia, and any of the three psychological symptoms being 21.9%, 18.7%, 31.2%, and 37.5%, respectively. The psychological status after re-positive showed a significant decrease in anxiety (P=0.023), an increase in depression, and a significant rise in insomnia (P=0.035). For those with no psychological symptoms during initial-positive, after re-positive, 5.88% reported anxiety, 5.88% reported depression, and 11.76% reported insomnia. For those who experienced only anxiety symptoms during initial-positive, after re-positive, 33.3% reported depression, and 33.3% reported insomnia. Conclusions: Our findings encompassed the urgent concern for anxiety in initial-positive COVID-19 patients, depression in re-positive COVID-19 patients, and insomnia in both initial and re-positive patients, hence enabling targeted interventions for appeasing the psychological burden of COVID-19 patients.